2014
DOI: 10.2174/1389202915666140221005023
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Proteostasis Upon Transition to Adulthood is Linked to Reproduction Onset

Abstract: Protein folding and clearance networks sense and respond to misfolded and aggregation-prone proteins by activating cytoprotective cell stress responses that safeguard the proteome against damage, maintain the health of the cell, and enhance lifespan. Surprisingly, cellular proteostasis undergoes a sudden and widespread failure early in Caenorhabditis elegans adulthood, with marked consequences on proteostasis functions later in life. These changes in the regulation of quality control systems, such as chaperone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 95 publications
(153 reference statements)
1
36
0
Order By: Relevance
“…Remodeling protein homeostasis (proteostasis) can be mediated by endocrine signals released from neurons or the reproductive system (Sala et al, ; Shai, Shemesh, & Ben‐Zvi, ). A well‐studied example of proteostasis remodeling is the early switch in the regulation of quality control networks seen at the onset of Caenorhabditis elegans reproduction, associated with a reduced folding capacity and stress response activation (Labbadia & Morimoto, ; Shemesh, Shai, & Ben‐Zvi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remodeling protein homeostasis (proteostasis) can be mediated by endocrine signals released from neurons or the reproductive system (Sala et al, ; Shai, Shemesh, & Ben‐Zvi, ). A well‐studied example of proteostasis remodeling is the early switch in the regulation of quality control networks seen at the onset of Caenorhabditis elegans reproduction, associated with a reduced folding capacity and stress response activation (Labbadia & Morimoto, ; Shemesh, Shai, & Ben‐Zvi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibited activity of steroid hormone signaling at the transition to reproductive adulthood results in a sharp decline in both folding capacity and stress activation, whereby the functions of various transcription factors regulating the expression of quality control machineries, including HSF‐1/HSF1, DAF‐16/FoxO, PHA‐4/FoxA, and SKN‐1/Nrf2, are modulated (Berman & Kenyon, ; Lapierre, Gelino, Melendez, & Hansen, ; Shemesh et al, ; Steinbaugh et al, ). This is associated with age‐dependent misfolding and the aggregation of various metastable proteins and a general decline in healthspan (Ben‐Zvi, Miller, & Morimoto, ; Chang, Kumsta, Hellman, Adams, & Hansen, ; David et al, ; Shai et al, ; Vilchez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the same systemic KD resulted in increased Q35 aggregation in another study (Scior et al, 2018). The respective outcome is likely to depend on the timing and strength of the KD, and to what extent it affects the folding of proteins other than Q35, both in the same tissue and in neighboring tissues, which may also influence muscle cell proteostasis through non-autonomous mechanisms (Morimoto, 2019; Shai et al, 2014). Our results clearly show that the impairment of the disaggregation machinery rescues the aggregation and toxicity of amyloid-like substrates, but at the same time negatively impacts the removal of amorphous aggregates or folding of metastable proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that aging in nematodes is accompanied by a decline in the ability of the organism to deal with misfolded proteins, and mount an efficient proteotoxic stress response (Ben-Zvi et al, 2009). The proteostasis collapse in nematodes occurs at a specific time frame of adulthood and is linked to the reproductive onset (Labbadia and Morimoto, 2015b;Shai et al, 2014;Shemesh et al, 2013). Furthermore, a specific chromatin state has been associated with the phenomenon (Labbadia and Morimoto, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…While many hallmarks of aging support the general notion of proteostasis collapse being a part of human aging, its occurrence in mammalian organisms has not been directly tested on a genomewide scale. Additionally, there is still debate whether the proteostasis collapse in nematodes is the result of damaged proteins that have accumulated throughout the life of the organism, or whether it is a programmed event (Labbadia and Morimoto, 2015a;Shai et al, 2014;Taylor and Dillin, 2011).…”
Section: Introductionmentioning
confidence: 99%